Industry 4.0 Impact on Intelligent Logistics and Manufacturing - Bányai, Tamás; Petrilloand Fabio De Felice, Antonella (IntechOpen, 2020)
Implementing Industry 4.0 technologies and solutions is a strategic objective of manufacturing and service companies to foster competitiveness on the global market. The Industry 4.0 as an industrial ecosystem is a potential glue that can hold interconnected logistics systems and value making chains together. This book offers a selection of papers that explain the impact of the fourth industrial revolution on intelligent manufacturing and logistics. Authors from ten countries (China, Colombia, Czech Republic, Hungary, Italy, Japan, Singapore, Slovakia, Spain, and USA) have published worked examples and case studies from their research in the field. The aim of this book is to help students at the level of BSc, MSc, and PhD level as well as managers and researchers, to understand and appreciate the concept, design, and implementation of Industry 4.0 solutions.